PERANCANGAN SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN TOOLS DI SMK NEGERI 3 BATAM MENGGUNAKAN METODE WATERFALL - Yasra, Refdilzon; Yunesman, Yunesman; Tri Widodo, Trenggono; August Saputra, Rezhy (SIGMA TEKNIKA, 2024)
Abstract SMK Negeri 3 Batam majoring Teknik Bisnis dan Sepeda Motor presently transaction for loan and returning tools from student practice in the workshop and Controlling the data of tool and inventory of tools done in manual or hardcopy used. This is will impact to the processing time for student preparing the tool for practicing in the laboratories due to loams and returns of tools time consuming. Interview with the students for improving the accuracy of data, conclude the need of Information system using the program application for loans and return tools to be more accurate and traceability of the tools. The stage to provide the system information for student loans and returns tool using the waterfall method. The designing the Application suing the dataflow diagram (DFD) and Entity Relationship Diagram (ERD). Design and implementation of the application using the Kodula apps, where not required the programming skills. Application established and generate with simple database. In the implementation got the feedback from student. They are more effective and less time consuming for loan and returns the tools. Traceability of the Tools equipment loans easy to verify by student that increasing the accountability of student to return the Tools. We are expected the Apps implemented at other schools and improve the speed and database capacity more better apps.